Gauging the assessment literacy of Malaysia’s home economics teachers: an empirical study (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
In the effort to develop a world class educational system for Malaysia, the knowledge and skill in classroom assessment has to be upgraded to allow teachers to carry out a more effective teaching and learning process. Thus, the objectives of this study were to measure the level of assessment literacy based on the Standard for Teachers’ Competence in Educational Assessment of Students (AFT, NCME, NEA, 1990) and also to identify differences in assessment literacy based on teachers’ experience practising competency-based assessment. The instrument used to measure Teacher’s Assessment Literacyconsisted of 41 multiple choice items with the reliability index (KR20) =.73. Primary data were gathered from questionnaires completed and returned by 187 home economic teachers teaching Vocational Subjects in Malaysian secondary schools . The result of One-Way ANOVA test indicated that there was a significant difference between teachers’ assessment literacy and their experience of practising competency-based assessment (F (2,184=3.46, p< .05). The findings reflected that Home Economics teachers in Malaysia’s secondary schools had an average level of assessment literacy. Therefore, there is an urgent need for continuous professional development courses involving classroom assessment for Home Economics teachers to improve their practices, in particular, competency-based assessment.